2011
DOI: 10.1016/j.ejpain.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio-economic status on pain and the perception of disability due to pain

Abstract: Pain is a major burden for society and a great challenge for public health. The aim of this study was to evaluate the association of socio-economic status (SES) with pain, and assess if there were socio-economic differences in the impairment due to pain, even when the same level of pain was reported. Data were sourced from the Austrian Health Interview Survey 2006-2007, a population based nation-wide survey with 15,474 respondents. SES, based on education, income and profession was inversely and gradually asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 38 publications
12
133
2
5
Order By: Relevance
“…The perception of pain is subjective and dependent on the individual, cultural and economic conditions of the patient (Dorner et al 2011). Measuring such a subjective experience as pain is difficult; therefore, in this study, the level of discomfort was rated in only four categories to simplify the rating of pain.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of pain is subjective and dependent on the individual, cultural and economic conditions of the patient (Dorner et al 2011). Measuring such a subjective experience as pain is difficult; therefore, in this study, the level of discomfort was rated in only four categories to simplify the rating of pain.…”
Section: Discussionmentioning
confidence: 99%
“…7 Poor compliance is associated with lack of awareness among personnel. 8 The other factors are personnal and organizational attitude towards interventions like hand washing, cost containment and logistical barriers. 9 The education regarding HAIs has a positive impact on retention of KAP in all categories of health workers to prevent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it does not consider the extent to which individuals' lives are affected by pain. As discussed, low OSS individuals tend to be more disabled by pain (Dorner et al, 2011;Portenoy, Ugarte, Fuller, & Haas, 2004), and experience lower life quality (Gerstle et al, 2001). Overall, these limitations suggest that future research should perhaps include subjective measures of pain and general health, whilst still including analgesic prescriptions as an objective measure.…”
Section: Analgesics Measurementioning
confidence: 99%
“…Saastamoinen, Leino-Arjas, Laaksonen, and Lahelma (2005) found employees in Helsinki with relatively low educational attainment and occupational class were most at risk of chronic/disabling pain, while Dorner et al (2011) report that people with lower OSS not only experience more severe pain, but also greater pain-related disability when severity is controlled for. Gerstle et al (2001) found that amongst Americans with chronic pain, low OSS was associated with lower perceived life quality.…”
Section: Oss and Painmentioning
confidence: 99%